Hubungan Ketenagakerjaan Dan Perubahan Struktur Ekonomi terhadap Kesejahteraan Masyarakat - Hukom, Alexandra (Jurnal Ekonomi Kuantitatif Terapan; 2014: Vol. 7, No. 2, Agustus 2014 (pp. 83-198)DO - 10.24843/JEKT.2014.v07.i02.p04, 2015)
This study aims to analyze the relationship between employment changes in the economic structure of the welfare of the people in Indonesia using Sobel test approach. Employment is an economic analysis of the behavior of workers and employers as well as their interaction on the labor market. Changes in the economic structure of an economic transformation from traditional to modern can be generally defined as a change in the economy related to the composition of demand, trade, production and other factors necessary to continously increase revenue and social welfare through an increase in income per capita . The results showed that the employment effect on welfare through structural change in Indonesia. This means that the presence of employment in the capitalist sector (non-agricultural) employment without reducing the agricultural sector led to increased surplus is then invested back into the capitalist sector. Therefore, the growth of these sectors leads to structural changes in the economy which in turn have an impact on improving people's welfare.
Keywords: Employment, changes in the economic structure, the welfare of society.